Transformation characteristics of pore structure of coal by freezing-thawing cycle - YUAN Junwei; XIA Jingyi; CHU Shaofei (Meikuang Anquan, 2022)
In order to improve the effect of the gas extraction, to explore the transformation characteristics of freezing and thawing cycle of coal pore, vacuum full anthracite coal samples of water are placed in cooler（-20 ℃）, the nuclear magnetic resonance T2 spectrum was used to analyze the cracking effect of different freezing -thawing cycles, and the pore structure changes of coal samples before and after freezing-thawing were studied. The results showed that the T2 spectrum area increased greatly during the first to third freeze -thaw cycles, and reached the maximum value of 42.41% in the third freeze -thaw cycle. The increase of T2 spectrum area of 4 to 9 freeze -thaw cycles decreases continuously, and the cracking effect of freeze -thaw cycles decreases continuously. In the process of the third freeze -thaw cycle, the change of pore structure is the largest, and the comprehensive analysis shows that the third freeze-thaw cycle is the best number of freeze-thaw cycles.